Applicant Preferences for Virtual Interviews: Insights from the 2020–21 Integrated Plastic Surgery Application Cycle. Issue 7 (29th July 2021) - Hemal, Kshipra; Sarac, Benjamin A.; Boyd, Carter J.; Runyan, Christopher M.; Gosman, Amanda A.; Janis, Jeffrey E.
Abstract : Background: The COVID-19 pandemic created an unprecedented residency application cycle that required the use of virtual interviews. The inaugural class of applicants participating in virtual interviews were surveyed concerning their preferences and suggestions for future application cycles. Methods: A survey was distributed to 349 individuals who applied for an integrated plastic surgery residency position at three institutions during the 2020–21 application cycle. Responses were analyzed to determine the most popular attributes of virtual interviews. Results: Response rate was 44%. Eighty-six percent of applicants valued having time to consider their interview offers before scheduling; however, nearly one-third felt the instructions provided by programs lacked clarity and did not abide by the American Council of Academic Plastic Surgeons guidelines. Eighty-two percent of applicants valued having a preinterview social, and most preferred smaller breakout rooms organized by themes. A short interview day (less than three hours) was associated with less applicant familiarity with the program, its people, and its location when compared with medium (three to seven hours) and long (more than seven hours) interview days ( P < 0.001 for all). Eighty percent of applicants preferred an interview day where they were placed into interview rooms by a program coordinator. Conclusions: The virtual interview format can be optimized in many ways to benefit both applicants and programs. The data presented in this article provide suggestions for future iterations of virtual interviews.